2017
DOI: 10.4236/jbcpr.2017.52005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Challenges in Financing Contractors for Public Sector Projects in Ghana

Abstract: Contractors working with the Public sector encounter numerous challenges in financing projects in Ghana. The challenges which have persisted over the years are both financial and managerial. This paper seeks to ascertain the extent to which contractors' challenges in acquiring funds to execute public sector projects have been solved. The study involved both qualitative and quantitative methods to ascertain the various strategies the contractors go through to obtain public sector projects focusing on the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Interest rate in Ghana averaged 18.08% from 2002 until 2018, with current benchmark interest rate at 17% [33]. With this high interest rate and huge collateral demands from banks, it become extremely difficult for construction firms to access loans [34].…”
Section: Economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest rate in Ghana averaged 18.08% from 2002 until 2018, with current benchmark interest rate at 17% [33]. With this high interest rate and huge collateral demands from banks, it become extremely difficult for construction firms to access loans [34].…”
Section: Economic Factorsmentioning
confidence: 99%
“…The incidence of delayed payment or non-payment of works done by construction firms is a major threat to the performance of the construction industry in Ghana. Ofori et al [34] asserted that effective and efficient financing of public sector projects in Ghana has been a challenge of the industry over a period with successive governments. One significant reason for construction project delays and sometimes leading to eventual abandonment of projects has been due to untimely honouring of certificate by client.…”
Section: Financial Factors (Unpaid Work/delayed Payment)mentioning
confidence: 99%
“…This makes governments adopt advance financing approach to infrastructure development. Ofori et al (2017) realized that contractors working with the public sector encounter numerous challenges in financing projects in Ghana revealed that inadequacy in accounting expertise leading to delayed payments and inadequate cash flow on the part of government, lack of credit worthiness and inadequate collateral security from contractors are key determinants to challenges associated with financing public sector projects in Ghana. This paper recommended the establishment of a Construction Development Authority (CDA), within the Ministry of Works and Housing to develop financial plans, policies and laws for this important sector of the economy.…”
Section: Effect Of Professionalism On Advance Financing Of Roadsmentioning
confidence: 99%
“…Matara [14] reported that construction firms face serious drawbacks in securing finance and these hurdles come majorly from high-interest rates and the small size of the majority of the firms that operate in the construction market. Ofori et al [7] reported that the delays in honouring payment certificates and meeting collateral requirements are a major drawback to the financing of projects. However, keeping good records of financial transactions, excellent capital base and improved revenue generation; have been highlighted as important to construction firms getting finances.…”
Section: Original Articlementioning
confidence: 99%